If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 2x + x = 13 Combine like terms: 2x + x = 3x -5 + 3x = 13 Solving -5 + 3x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 13 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 13 + 5 3x = 13 + 5 Combine like terms: 13 + 5 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 1/6t=12 | | 2v^-1*u^-1/2v^1/2 | | 2x-5+3a-5x+10= | | 23/11.5 | | 1.82x+4=5.5x-1.82x | | (5b)*(9x)= | | 8/4x-3=19 | | 1/3x3.14x1x1.2 | | 25=5(f-32)/9 | | 11y^2-47y+12=0 | | 15+y=90 | | 2/0w=5/6 | | 5(y+3)=7y+15 | | 10g=4/86 | | 3(3x+8)-x=8 | | 3(4x+5)+2=3 | | 19-8d=-17 | | 10g=-4/6 | | 2x+7y=126 | | m/8=16 | | 11x^2-47y+12=0 | | 12-17=89 | | -5+1/4m=-7 | | 72=x+15 | | 1/2(6x+4)=2x-11 | | 4y^2-15y+9=0 | | 18-3x(4+(-8))+5x=10x-2 | | 2(x+-9)=-10 | | -5+1/4(-2)=-7 | | 8(3-y)-4=-(2-y)-9y | | 2m+1/3-m-6/4=2m+4/8+2 | | x^2+7xy^2=0 |